Numerical investigation of various configurations of nano-enhanced latent heat thermal energy storage - Laouer, Abdelghani; Atia, Aissa; Teggar, Mohamed; Arıcı, Müslüm; Mohd Rosli, Mohd Afzanizam (Elsevier Ltd, 2025)
Design and optimization of flexible and efficient energy storage units is considered as potential for enhancing energy efficiency of thermal systems which significantly contributes to energy savings as well as mitigation of emissions. This study investigates a new configuration of the melting process of nano-enhanced phase change materials (NePCM) inside a square cavity during simultaneous charging (two horizontal heating tubes) and discharging (a central horizontal cold tube). The study investigated the performance of various tubes layouts. The Lattice Boltzmann Method is applied to solve the dimensionless governing equations of the system. Different effective parameters are analyzed, including the Rayleigh number (Ra), heating tube positions, NPs concentrations, and melting times. The findings demonstrate that both heat transfer and melting processes are significantly enhanced in all studied cases with increasing Ra and NPs concentrations. The analysis revealed that positioning the hot tubes centrally within the upper and lower sections provides the most efficient arrangement, reducing the charging time by up to 75.5 %. Furthermore, adding NPs at concentrations of 1 %, 3 %, and 5 % increases the melting rate by 3.33 %, 10.17 %, and 19.12 %, respectively, compared to the melting time without NPs. These findings offer insights for designing flexible and efficient latent heat thermal energy storage systems.